EFFECTIVE METHOD OF TEACHING READING (A CASE STUDY) - Ariandika, Ahmad Girsa; Kartikawati, Dina (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
Students usually get difficulties in learning English subject. Especially for reading section. Teaching reading is not as simple as people think. They should have any more practice and should enlarge their knowledge to deliver reading materials especially at senior high school grade. Researcher found that the English teachers used interesting method that students can learn about reading text in a good condition.Based on the explanation above, the aim of this research is to know what method used in teaching reading applied by English teachers at tenth grade, and how the method is used in teaching reading. This study is a descriptive qualitative which observe tenth grade students of SMAN 1 Tulungagung. The data collected through three methods, they were observations, interview and the researcher himself.The result of this research is the English teachers used guided reading method to deliver the materials in teaching reading. In teaching and learning process, the English teachers gave guidance, direction and information continously from the English teachers to the students.